EVALUATION OF REFERENCE INTERVAL OF SERUM LIPID PROFILE IN RURAL AREA OF KONKAN REGION FROM MAHARASHTRA STATE - ARVIND S. YADAV; PRASAD V. KHODKE (International Journal of Pharma and Bio Sciences, 2015)
The aim of the study was to evaluate the reference interval of serum lipid profile from rural area of Konkan region of Maharashtra state. Study Design is a retrospective study. Serum lipid profile parameters were estimated by standard methods on Transasia Erba -200 Fully Automated Chemistry Analyser using Erba Diagnostic kits manufactured by Transasia Biomedical Pvt. Ltd. The present study includes total 554 healthy controls (330 males and 224 females) in the age group of 20 to 45 years. The serum total cholesterol levels in males were 160.09±25.25mgs/dl and in females were 153.51±33.16 mgs/dl. The serum triglyceride levels in males were 129.07 ± 45.87mgs/dl and in females were 129.88± 51.43 mgs/dl and HDL – Cholesterol levels in males were 40.35± 13.04mgs/dl and in females were 47.84± 14.30 mgs/dl. The statistical analysis was done by student’s t-test. The serum total cholesterol is lower in females as compared to males but it was found non-significant. The significant difference was observed in HDL – cholesterol levels in males and females from the same region. Conclusion: In the present study serum total cholesterol, triglycerides, LDL and VLDL – Cholesterol were non-significant in male as compared to females. It was found that HDL- cholesterol levels were significantly higher in females as compared to males. This may be because of estrogen levels in female, which increases HDL- Chloesterol levels. The present study further suggests that the lipid profile values obtained in this study can be used as the reference values for rural area of Konkan region of Maharashtra state.